2008
DOI: 10.5551/jat.e545
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pi-induced Vascular Calcification - Regulation of Growth Arrest-Specific Gene 6 (Gas6)-Mediated Survival Pathway

Abstract: Vascular calcification is clinically important in the development of cardiovascular disease. It has been suggested that apoptosis is one of the processes regulating calcification in vascular smooth muscle cells (VSMC). In this review, we discuss the role of apoptosis in inorganic phosphate (Pi)-induced calcification, focusing on regulation of the survival pathway mediated by growth arrest-specific gene 6 (Gas6). Further, we mention the beneficial effect of statins mediated by inhibition of apoptosis which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Statins, potent lipid lowering agents, have been shown to exert antioxidant effects and improve endothelial function in uremic animals [10] and in maintenance hemodialysis (HD) patients [11]. Statins have also been shown to have antithrombotic properties [12] and to prevent vascular calcification in experimental models [13]. However, it is not known whether these properties enable statins to offer any protection against the CUA development.…”
Section: Introductionmentioning
confidence: 99%
“…Statins, potent lipid lowering agents, have been shown to exert antioxidant effects and improve endothelial function in uremic animals [10] and in maintenance hemodialysis (HD) patients [11]. Statins have also been shown to have antithrombotic properties [12] and to prevent vascular calcification in experimental models [13]. However, it is not known whether these properties enable statins to offer any protection against the CUA development.…”
Section: Introductionmentioning
confidence: 99%
“…(1,(5)(6)(7)(8)(12)(13)(14)(15)(16)(17)(18) Our results are the first to relate DNA methylation with the loss of smooth muscle lineage marker SM22a in VSMCs incubated with high phosphate. SM22a promoter methylation decreases SM22a gene expression, and this fact could facilitate phenotypic transition of VSMCs to osteoblast-like cell.…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies have shown that VCs are a well-regulated process that involves transdifferentiation of vascular smooth muscle cells (VSMCs) into osteoblast-like cells capable of synthesizing the proteins required for calcification. (5)(6)(7) High phosphate concentration seems to play an essential role in the calcification process. In vitro studies have demonstrated that phosphate transport into the cell is a necessary step for calcification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular calcification is one form of arteriosclerosis, and vascular calcification, which has been associated with osteochondrogenic differentiation of vascular smooth muscle cells [3,4,5], is considered to have some points in common to physiological calcification of the bone. It has been reported that serum phosphate induces vascular smooth muscle cell apoptosis and osteochondrogenic differentiation [4,6], and that serum phosphate levels are considered to be associated with vascular calcification [7,8,9]. In CKD patients, chronic inflammation and accelerated oxidative stress are common, and can also induce vascular calcification [10,11,12].…”
Section: Introductionmentioning
confidence: 99%